2015
DOI: 10.1371/journal.ppat.1005001
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Murine Gamma Herpesvirus 68 Carrying KSHV G Protein-Coupled Receptor Induces Angiogenic Lesions in Mice

Abstract: Human gamma herpesviruses, including Kaposi’s sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV), are capable of inducing tumors, particularly in in immune-compromised individuals. Due to the stringent host tropism, rodents are resistant to infection by human gamma herpesviruses, creating a significant barrier for the in vivo study of viral genes that contribute to tumorigenesis. The closely-related murine gamma herpesvirus 68 (γHV68) efficiently infects laboratory mouse strains and establishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…Murine gamma herpesvirus 68 (MHV68) viruses were propagated in BHK21 cells (Zhang et al, 2015b). Herpes simplex virus 1 (HSV-1) WT and UL37C819S recombinant viruses were propagated using Vero cells.…”
Section: Star Methodsmentioning
confidence: 99%
“…Murine gamma herpesvirus 68 (MHV68) viruses were propagated in BHK21 cells (Zhang et al, 2015b). Herpes simplex virus 1 (HSV-1) WT and UL37C819S recombinant viruses were propagated using Vero cells.…”
Section: Star Methodsmentioning
confidence: 99%
“…There are few available models for KSHV, but in a mouse model of KSHV and in patients with KSHVassociated malignancies, exosomal miRNAs of the host and those encoded by KSHV, including the miR-17-92 cluster, were successfully detected. Furthermore, the characterization and analysis of exosomal miRNAs, their targets, and endothelial cells revealed that exosomes containing a wide variety of miRNAs play a functional biological role in signaling pathways linked to the pathogenesis of KSHV and its phenotypic characteristics (Chugh et al, 2013;Zhang et al, 2015a). Hence, distinct exosomal miRNAs are expected to represent a portion of the paracrine signaling mechanism, which is the hallmark of KSHV tumorigenesis.…”
Section: Exosomes In Gamma Herpesvirus Infectionmentioning
confidence: 99%
“…An elegant study employed an endothelial cell specific retroviral delivery system to demonstrate that the expression of vGPCR, among multiple suspected KSHV oncogenes, was sufficient to induce KS-like tumors in mice [29]. Murine gamma herpesvirus 68 (γHV68) carrying KSHV vGPCR, rather than murine γHV68 GPCR (mGPCR), induced angiogenic lesions in virus-infected mice, offering a murine model of viral oncogenesis in the context of true viral infection [30]. Together, these studies support that KSHV vGPCR may significantly contribute to the sarcomagenesis of KSHV-infected patients.…”
Section: Kshv Vgpcrmentioning
confidence: 99%
“…It is only expressed in a small subset of cells (∼5%) in human KS or KS-like lesions in model animals [25, 29, 30, 33]. To reconcile this paradox, it is postulated that dysregulated abortive lytic replication may permit the expression of a subset of lytic genes, including vGPCR, to avoid late gene expression and lysis of host cells.…”
Section: Kshv Vgpcrmentioning
confidence: 99%
See 1 more Smart Citation